Glomerular tip adhesions predict the progression of IgA nephropathy - Maeda, Kunihiro (BMC Nephrol, 2013)
BACKGROUND: Focal segmental glomerulosclerosis-like lesions have been proposed to be predictive factors for IgA nephropathy. This single center, retrospective cohort study was designed to clarify which clinical and pathological factors are predictive of decreased estimated glomerular filtration rate (eGFR) at 5 and 10 years in IgA nephropathy patients. METHODS: Of the 229 patients with IgA nephropathy who were admitted to Aichi Medical University Hospital between 1986 and 2010, 57 were included in this study during the 5 to 10 years after renal biopsy. Clinical, laboratory, and pathological parameters were analyzed by multiple linear regression analysis with backward elimination to determine independent risk factors. After identifying such factors, we compared patients with and without each factor using the Student’s t test, Wilcoxon test, or Mann–Whitney U test. RESULTS: Four variables were identified as predictive factors for progression of IgA nephropathy: initial eGFR (p = 0.0002), glomerular tip adhesion (p = 0.004), global sclerosis (p = 0.019), and diastolic blood pressure (p = 0.024). The annual decrease in eGFR of patients with (n = 9) or without glomerular tip adhesions (n = 48) was 4.13 ± 3.58 and 1.49 ± 2.89 ml/min/1.73 m2, respectively (p = 0.015). Serum total cholesterol levels were 231 ± 45 mg/dl and 196 ± 42 mg/dl, respectively (two-sided p = 0.064; one-sided p = 0.032). CONCLUSIONS: The presence of glomerular tip adhesions predicts the progression of IgA nephropathy. High levels of serum total cholesterol may affect glomerular tip adhesions.